3 - On Prospective: Development and a Political Culture of Time: 10.4314/ad.v29i1.22185 - Diagne, Souleymane Bachir (Africa Development, 2004)
This paper interprets the African development crisis as a crisis of initiative. Right after the Lagos Plan of Action was adopted in 1980, came in 1981 the Berg Report on which were built the Structural Adjustment Programmes that African countries were soon forced to adopt. Unsurprisingly, the weakened states and impoverished populations lost sight of what was the driving force behind the Lagos Plan of Action; that is, a long-term perspective, a horizon for development. Along with developmental perspective, what was thus lost was nothing less than meaning. This crisis of meaning is felt today particularly in Africa's youngest generations who perceive themselves as futureless unless they emigrate. Because meaning flows from the future to the present, and is about shaping the future, this is a philosophical reflection on time which is also a call for the reconstruction of meaning through the cultivation of 'a prospective capacity' in our African societies. Analyzing this philosophical concept as it was developed by Gaston Berger, this paper argues that such a cultivation of 'prospective' amounts to fostering a political culture of time which is to be understood in total contrast with the ethnological approach attached to a so called 'African' notion of time.